PERTUMBUHAN DAN PRODUKSI TIGA VARIETAS KACANG KEDELAI TERHADAP PERENDAMAN DENGAN GIBERELIN - Harahap, Ariani Syahfitri; Wasito, Muhammad; Siregar, Maimunah; Ariska, Lulu (University of Prof. Dr. Hazairin, SH, 2024)
The aim of this research was to determine the growth and production of three varieties of soybeans when soaked in gibberellins. The research was carried out in Sampecita Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra, which was carried out from January to May 2024. This research used an experimental design, namely a factorial Randomized Group Design (RAK) consisting of 2 treatments, namely varieties (Ring 1, Dega 1 and Devon 1) and gibberellin immersion, namely: 0 ppm, 50 ppm, 100 ppm and 150 ppm which were repeated 3 times time. The research data were analyzed and continued with the Duncan's mean difference test (DMRT). The results showed that the growth and production of soybean plants for varieties showed a significant effect on the parameters of plant height, flowering age, number of productive branches, number of pods per sample, number of pods per plot, weight of seeds per sample, weight of seeds per plot, and weight of 100 seeds, while the soaking treatment with gibberellin showed no significant effect on all observed parameters. The Dering 1 variety and gibberellin concentrations of 50 ppm and 100 ppm showed a fairly good effect on the growth and production of soybean plants.